Anti-P-glycoprotein conjugated nanoparticles for targeting drug delivery in cancer treatment - Iangcharoen P. (2014)
Targeting therapeutics to specific sites can enhance the efficacy of drugs, reduce required doses as well as unwanted side effects. In this work, using the advantages of the specific affinity of an immobilized antibody to membrane P-gp in two different nanoparticle formulations were thus developed for targeted drug delivery to multi-drug resistant cervical carcinoma (KB-V1) cells. Further, this was compared to the human drug sensitive cervical carcinoma cell line (KB-3-1) cells. The two nanoparticle preparations were: NP1, anti-P-gp conjugated with poly (DL-lactic-coglycolic acid) (PLGA) nanoparticle and polyethylene glycol (PEG); NP2, anti-P-gp conjugated to a modified poloxamer on PLGA nanoparticles. The cellular uptake capacity of nanoparticles was confirmed by fluorescent microscopy. Comparing with each counterpart core particles, there was a higher fluorescence intensity of the targeted nanoparticles in KBV1 cells compared to KB-3-1 cells suggesting that the targeted nanoparticles were internalized into KB-V1 cells to a greater extent than KB-3-1 cell. The results had confirmed the specificity and the potential of the developed targeted delivery system for overcoming multi-drug resistance induced by overexpression of P-gp on the cell membrane. © 2011 The Pharmaceutical Society of Korea and Springer Netherlands.